Cold-mixed drainage asphalt mixture for airport cement pavement and preparation method thereof

CN122878069APending Publication Date: 2026-10-09CHENGDU UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611116111.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

该技术在乳化阶段采用特定乳化剂和稳定剂解决了聚合物与沥青的相容性问题,在破乳后能显著提升沥青膜的界面粘结强度与内聚韧性,从根本上克服了传统冷拌混合料强度低的行业通病

Benefits of technology

1、实现了冷拌条件下性能对标热拌:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a cold-mixed drainage asphalt mixture for airport cement pavement and a preparation method thereof. The mixture comprises modified emulsified asphalt, mineral aggregate, filler and fiber in a specific ratio. The application improves the bonding toughness and strength of the emulsified asphalt after demulsification through a polymer modifier. The application realizes an optimized void ratio of 16%-20% through fine gradation with a maximum nominal particle size of 13 mm, guarantees efficient drainage under a low cross slope, and is supplemented by fiber reinforcement and toughening. The mixture can be directly constructed at normal temperature (10-40 DEG C), and energy consumption and carbon emission are reduced by more than 80%. After molding, the permeability coefficient is greater than or equal to 2000 mL / min, the Marshall stability is greater than or equal to 5 kN, and the anti-cracking performance is greater than or equal to 1200 times. The performance indexes reach those of traditional hot-mixed drainage asphalt mixture, and the application provides a green and high-performance internal drainage solution for airport cement pavement, can significantly reduce water damage, and prolongs the service life of the pavement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a cold-mix drainage asphalt mixture and its preparation method specifically for airport cement pavement. Background Technology

[0002] Water damage to the pavement is a significant factor affecting airport pavement performance and operational safety. Essentially, surface water seeps in through joints or cracks and cannot be effectively drained. Under the dynamic water pressure generated by aircraft wheels, this leads to serious defects such as pumping, misalignment, slab separation, and slab breakage, ultimately impacting aircraft operational safety. Therefore, constructing an efficient internal drainage system for the pavement, ensuring no water accumulation between the concrete surface layer and the base layer, and maintaining effective adhesion between the two are crucial measures to extend the service life of the pavement.

[0003] Currently, road engineering often uses porous asphalt stabilized crushed stone drainage (ATPB-25) or porous asphalt mixture (PAC) as the drainage layer within the pavement structure system. The aim is to quickly drain water that has entered the pavement structure, reducing the erosion of the base course surface. However, directly applying this technology to airport concrete pavement presents a significant technological gap. Comparing the requirements of the "Technical Standards for Civil Airport Flight Areas" (MH5001-2021), the "Code for Design of Drainage for Civil Airports" (MH / T 5036-2017), and the "Code for Design of Drainage for Highways" (JTG / T D33-2012), the drainage base courses of airport runways and highway pavements differ fundamentally in terms of service environment and mechanical requirements. (i) High safety targets for airport runways. The effectiveness of drainage is directly related to airport operational safety and facility durability, requiring runway surfaces to have good friction characteristics. Airports require runway surface water depth to be ≤3mm, while highways allow water depth to be ≤5~10mm, placing higher demands on drainage efficiency; (ii) Airport runways have long drainage paths and gentle cross slopes. Airport runways can be up to 45 meters wide, with a single-sided drainage length of about 22.5 meters, which is significantly higher than the single-sided drainage length of about 15 meters for a road (based on an eight-lane dual carriageway). However, the cross slope of airport runways is ≤1.5%, which is significantly lower than the lateral slope of roads (1.5% to 4%), resulting in a serious lack of drainage driving force. (III) Airport drainage-type base layers are deep and subject to greater load stress. The thickness of the airport cement concrete surface layer is approximately 40cm, while that of the highway cement concrete surface layer is approximately 30cm. The aircraft load (taking a B747-400 as an example, with a single wheel load of 230.42kN and a tire pressure of 1.379MPa) is much greater than the highway vehicle load (design axle load of 100kN and tire pressure of 0.7MPa). The load stress is transmitted through the concrete slab, resulting in a lower bending tensile stress at the bottom of the airport concrete slab (approximately 2.5MPa) that is approximately greater than that at the bottom of the highway concrete slab (approximately 1-1.5MPa).

[0004] (iv) High requirements for construction environment and environmental protection. Airport flight area pavements are mostly made of cement concrete, while highway pavements are generally made of hot-mix asphalt concrete, with very few using cement concrete. The construction machinery, equipment, mixing plants, and other facilities and equipment corresponding to these two construction methods are completely different. Traditional hot-mix drainage asphalt mixtures have problems such as high energy consumption and high emissions. Furthermore, if hot-mix drainage asphalt base courses are to be constructed on airport cement concrete pavements, the construction unit needs to add an asphalt mixing plant, resulting in poor economic and environmental benefits.

[0005] In summary, airport drainage base courses face a triple challenge: high requirements for drainage efficiency, high requirements for mechanical properties, and high requirements for environmental protection during construction. While cold-mix drainage asphalt mixtures possess potential advantages in terms of being green and low-carbon, existing technologies generally suffer from fatal flaws such as low mechanical strength, poor crack resistance, and insufficient durability. The fundamental reason lies in the weak adhesion of conventional emulsified asphalt after demulsification and the lack of a mixture gradation and structural design that matches the heavy loads, gentle slopes, and long drainage paths of airports. Therefore, developing a cold-mix drainage asphalt mixture that combines high-efficiency drainage, high strength and durability with normal-temperature construction characteristics is key to solving the aforementioned technical problems. Currently, there is no mature technology available for preparing drainage asphalt mixtures using high-performance emulsified asphalt suitable for airport drainage base courses.

[0006] Therefore, this patent application is filed. Summary of the Invention

[0007] To address the service environment and performance bottlenecks of drainage-type base courses for airport cement pavements, a multi-component synergistic system of "high-performance emulsified asphalt-specialized mineral aggregate gradation-fiber reinforcement" is proposed. This invention achieves comprehensive performance of cold-mix asphalt at room temperature comparable to or even surpassing that of traditional hot-mix asphalt through the following technological innovations: 1. Polymer Network Modified Asphalt Technology: This technology introduces specific types of polymer modifiers (SBS, epoxy resin, polyurethane, etc.) to construct a three-dimensional network structure within the asphalt. During the emulsification stage, specific emulsifiers and stabilizers address the compatibility issue between the polymer and asphalt. After demulsification, it significantly improves the interfacial bonding strength and cohesive toughness of the asphalt film, fundamentally overcoming the industry-wide problem of low strength in traditional cold-mix asphalt.

[0008] 2. Airport-Adaptive Open-Graded Abrasive Design: An innovative open-graded aggregate with a nominal maximum particle size of 13mm was designed. Compared to conventional drainage asphalt mixtures, this aggregate features smaller particle size, more uniform porosity, and a denser structure. A porosity of 16%~20% ensures high water conductivity (permeability coefficient ≥2000 mL / min) under low cross slopes and long drainage paths. Furthermore, the smaller particle size and superior abrasive interlocking structure allow it to withstand greater flexural stress at the bottom of the slab, perfectly suited to heavy-load airport conditions.

[0009] 3. Fiber-asphalt-aggregate ternary composite reinforcement: By adding specific fibers, a micro-reinforced network is formed in the mixture, which effectively inhibits the initiation and propagation of cracks and improves the crack resistance performance (OT test) of the material to more than 1200 cycles, solving the fatigue cracking problem of drainage base course under repeated bending and tension.

[0010] The first objective of this invention is to provide a cold-mixed drainage asphalt mixture for airport cement pavement, comprising modified emulsified asphalt, mineral aggregates, fillers, and fibers; The cold-mixed drainage asphalt mixture for airport cement pavement comprises the following components by weight: 5.4 to 9 parts modified emulsified asphalt, 90.8 to 95.6 parts mineral aggregates and fillers, and 0.2 to 0.4 parts fiber. In this invention, the mineral aggregates and fillers primarily form a large-void, open-graded skeleton, providing channels for water infiltration. Through reasonable gradation design, it can meet the porosity requirements (16% to 20%) of airport drainage base courses and achieve efficient drainage.

[0011] The modified emulsified asphalt comprises the following components in parts by weight: 45 to 62 parts base asphalt, 0.8 to 1.5 parts emulsifier, 3 to 5 parts polymer modifier, 0.2 to 0.5 parts by weight of the sum of stabilizer and defoamer, and 35 to 50 parts water.

[0012] As a preferred design, the base asphalt is at least one of grade 70 base asphalt, grade 90 base asphalt, PG64-22 base asphalt, and PG58-22 base asphalt.

[0013] As a preferred design, the emulsifier is a cationic emulsifier, preferably a quaternary ammonium salt cationic emulsifier, which can provide a more uniform droplet distribution and better stability. This type of emulsifier imparts a positive charge to the surface of asphalt droplets, resulting in strong electrostatic adsorption with the normally negatively charged mineral aggregates, thereby significantly improving the early strength and water-resistant spalling resistance of the mixture.

[0014] As a preferred design, the polymer modifier is at least one selected from styrene-butadiene-styrene block copolymer, polyethylene, styrene-butadiene rubber latex, polyurethane, and epoxy resin. Each of these modifiers has its own characteristics: SBS and rubber latex significantly improve elastic recovery; epoxy resin and polyurethane can form a thermosetting network, greatly increasing bond strength. By incorporating 50% of the polymer modifier composition into a blend of 50% SBS and rubber latex, 70%–80% epoxy resin and 20%–30% SBS, or 70%–80% polyurethane and 20%–30% SBS, a synergistic toughening effect combining rigidity and flexibility can be achieved.

[0015] As a preferred design, the stabilizer is at least one of calcium chloride and polyvinyl alcohol, whose main function is to improve the storage stability of the emulsion; the defoamer is organosilicon, used to reduce bubbles in the preparation process and ensure that the asphalt droplets are uniform and fine.

[0016] In a preferred design, the sum of the mass of the mineral aggregates and fillers accounts for 90.8% to 95.6% of the total mass of the cold-mixed drainage asphalt mixture, the fiber accounts for 0.2% to 0.4% of the total mass of the cold-mixed drainage asphalt mixture, and the high-performance modified emulsified asphalt accounts for 5.4% to 9% of the cold-mixed drainage asphalt mixture.

[0017] As a preferred design, the mineral aggregate is at least one of limestone, granite, and basalt; And / or the filler is mineral powder; And / or, the fiber is polyester fiber, lignin fiber, or nanocellulose.

[0018] As a preferred design, the synthetic gradation range of the mineral aggregate satisfies the following conditions: 100% pass rate for a 16.0 mm sieve, 90%~100% pass rate for a 13.2 mm sieve, 60%~80% pass rate for a 9.5 mm sieve, 12%~30% pass rate for a 4.75 mm sieve, 10%~22% pass rate for a 2.36 mm sieve, 6%~18% pass rate for a 1.18 mm sieve, 4%~15% pass rate for a 0.6 mm sieve, 3%~12% pass rate for a 0.3 mm sieve, 3%~8% pass rate for a 0.15 mm sieve, and 2%~6% pass rate for a 0.075 mm sieve.

[0019] This gradation design achieves a porosity (16%–20%) and efficient drainage effect that meets the requirements of airport drainage base courses. This gradation design is one of the core features of this invention. Compared to conventional drainage asphalt mixtures (such as PAC-13 and ATPB-25), this invention imposes stricter limits on the content of intermediate particle size (2.36mm–4.75mm) and fine particles (<0.075mm): the appropriate intermediate particle size ensures the stability of the skeleton and the connectivity of the pores; while the higher mineral powder content increases the specific surface area of ​​the asphalt mastic, providing valuable initial bonding strength under cold-mix conditions, which is key to achieving room-temperature construction without loosening.

[0020] This invention achieves the drainage requirements of the internal structure of airport pavement by optimizing the aggregate gradation design, namely, a drainage asphalt mixture for airport concrete pavement with a smaller nominal maximum particle size (13mm), optimized mixture porosity (16-20%), smaller construction thickness (3-4cm), and convenient construction (no heating required).

[0021] The second objective of this invention is to provide a method for preparing a cold-mixed drainage asphalt mixture for airport cement pavement as described in any of the above claims, comprising the following steps: (1) Heat the base asphalt to 140-165℃, add the polymer modifier one by one, stir at high speed for 40-60 min at constant temperature, and develop at constant temperature for 60-120 min to make modified asphalt; (2) Mix the emulsifier with water, heat to 50-60℃, stir until completely dissolved, adjust the pH to 2-3, add the stabilizer, and obtain the emulsifier solution; (3) Mix the preheated modified asphalt in step (1) with the emulsifier solution obtained in step (2) in proportion, and shear emulsify at 140-160℃. Add defoamer during the process to obtain high-performance modified emulsified asphalt. (4) After mixing the high-performance modified emulsified asphalt with dry mineral aggregates, fillers and fibers at room temperature according to the specified ratio, the mixture is then laid and compacted in sequence. (5) Wait for the emulsified asphalt to break down and solidify, and then cure and shape it.

[0022] As a preferred design, the constant temperature high-speed stirring rate in step (1) is 8000-12000 rpm, and the thickness obtained after rolling in step (4) is 4~6 cm.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. Achieved performance benchmarks for hot mixing under cold mixing conditions: The construction temperature is reduced from 140-180℃ for traditional hot-mix asphalt to ambient temperature (10-40℃), reducing energy consumption and carbon emissions by more than 80%, and eliminating the need for additional hot-mix plants, making it perfectly suited for airport construction conditions; the resulting mixture has a Marshall stability of ≥5kN, and the number of crack resistance tests (OT) exceeds 1200 times, with key mechanical indicators reaching and surpassing those of traditional hot-mix drainage asphalt mixtures.

[0024] 2. Performance regulation design was carried out for airport operating conditions: With a porosity of 16%-20% and a permeability coefficient ≥4000 mL / min, it can reduce water retention in the base layer by more than 80%, ensuring efficient drainage on low cross slopes and long paths. Through polymer interpenetrating networks and fiber reinforcement, it enhances the excellent crack resistance and fatigue resistance of the mixture, and can withstand tensile stress at the bottom of the slab of more than 2.5MPa, significantly reducing the risk of voids and breakage at the bottom of the concrete slab. The 3-4cm thin layer design can effectively drain water and also serve as a stress absorption layer, which can reduce the temperature warping stress of the concrete slab by more than 20% and extend the service life of the pavement by more than 50%.

[0025] 3. Excellent overall performance Not only does it possess excellent drainage and mechanical properties, but its water stability indicators, such as residual stability and freeze-thaw splitting strength ratio, also meet high standards, ensuring reliability and durability in the long-term service environment of airport pavements. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. The illustrative embodiments and descriptions of this invention are only used to explain this invention and are not intended to limit this invention. Example 1:

[0027] The cold-mix drainage asphalt mixture in this embodiment includes high-performance modified emulsified asphalt, mineral aggregates, fillers, and fibers. The solid content of the high-performance modified emulsified asphalt is 64%, accounting for 6.6% of the total mass of the cold-mix drainage asphalt mixture. The combined proportion of mineral aggregates and fillers is 93.1%, and the fiber accounts for 0.3%.

[0028] The components of the high-performance modified emulsified asphalt are as follows: 60 parts of No. 70 base asphalt, 1.2 parts of alkyl trimethyl quaternary ammonium salt cationic emulsifier, 3 parts of epoxy resin modifier, 0.2 parts of calcium chloride stabilizer, 0.3 parts of organosilicon defoamer, and 35.3 parts of deionized water.

[0029] The mineral aggregate is limestone, the filler is limestone powder, and the fiber is polyester fiber. The mineral aggregate gradation is based on a particle size ratio of (10~15) mm:(6~10) mm:(0~5) mm = 15%:46%:36%. The gradation must meet the requirements of 100% passing through a 16.0 mm sieve, 96.9% passing through a 13.2 mm sieve, and 67.9% passing through a 9.5 mm sieve (see Table 1 for specific gradation data).

[0030] Table 1. Synthetic gradation table of mineral aggregates in raw materials

[0031] The preparation process of the cold-mix drainage asphalt mixture in this embodiment is as follows: (1) Heat the base asphalt to 160°C, add the epoxy resin modifier one by one, stir at a speed of 10,000 rpm for 60 min at constant temperature using a high-speed shear machine, and develop at constant temperature for 120 min to make modified asphalt. (2) Mix the alkyltrimethyl quaternary ammonium salt cationic emulsifier with deionized water, heat to 60°C, stir until completely dissolved, adjust the pH to 3, add a stabilizer, and obtain a mixed emulsion; (3) The preheated modified asphalt obtained in step (1) and the mixture in step (2) are pumped into the grinding chamber of a high-speed colloid mill in proportion and sheared and emulsified at 160°C. During the process, defoamer is added to prepare high-performance modified emulsified asphalt. (4) The mineral aggregate is prepared according to the synthetic gradation and dried, dry-mixed for 5s, and the high-performance modified emulsified asphalt and fiber obtained in step (3) are added and stirred for 90s. Finally, 3% mineral powder is added and stirred for 90s to obtain a uniformly mixed cold-mixed drainage asphalt mixture.

[0032] (5) Add to the specimen mold, rotate and compact or roll to form a standard specimen, and conduct performance tests. The test results and index requirements are summarized in Table 3.

[0033] The results show that the porosity of the asphalt mixture in this embodiment reaches 18.6%, the permeability coefficient reaches 4000 mL / min, and the permeability performance is good; the residual stability, scattering loss rate and freeze-thaw splitting strength ratio can all meet the expectations, and it has good water stability; the crack resistance performance (OT test) test loads more than 1400 times, and it has good crack resistance and durability. Example 2:

[0034] This embodiment of the cold-mix drainage asphalt mixture includes high-performance modified emulsified asphalt, mineral aggregates, fillers, and fibers. The high-performance modified emulsified asphalt has a solid content of 55% and accounts for 7.27% of the total mass of the cold-mix drainage asphalt mixture. Mineral aggregates and fillers account for 92.53%, and fibers account for 0.2%.

[0035] The components of the high-performance modified emulsified asphalt are as follows: 50 parts of No. 90 base asphalt, 1.5 parts of alkyltrimethyl quaternary ammonium salt cationic emulsifier, 4 parts of SBS IC modifier, 0.5 parts of calcium chloride and organosilicon, and 44 parts of deionized water.

[0036] The preparation process of the cold-mix drainage asphalt mixture in this embodiment is as follows: (1) Heat the base asphalt to 140°C, add SBS IC modifier, stir at 10000 rpm for 60 min, and keep it at a constant temperature for 120 min to obtain modified asphalt.

[0037] (2) Mix the emulsifier with deionized water and heat to 60°C. After stirring to dissolve, adjust the pH to 2.5 and add calcium chloride to obtain the emulsifier solution.

[0038] (3) The modified asphalt and emulsifier solution are mixed in proportion, sheared and emulsified at 180°C, and an organosilicon defoamer is added to obtain high-performance modified emulsified asphalt.

[0039] (4) After the mineral aggregate is dried, it is dry-mixed for 5 seconds, and high-performance modified emulsified asphalt, fiber and mineral powder are added in sequence and stirred for 90 seconds to obtain the mixture.

[0040] (5) Roller-rolled rutted slab specimens were cured and molded, and performance tests were conducted. The test results and index requirements are summarized in Table 3.

[0041] The results show that the porosity of the asphalt mixture in this embodiment reaches 17.5%, the permeability coefficient reaches 3500 mL / min, and the permeability performance is good; the residual stability, scattering loss rate and freeze-thaw splitting strength ratio can all meet the expectations, and it has good water stability; the crack resistance performance (OT test) test loads more than 1300 times, and it has good crack resistance and durability. Example 3:

[0042] This embodiment of the cold-mix drainage asphalt mixture includes high-performance modified emulsified asphalt, mineral aggregates, fillers, and fibers. The high-performance modified emulsified asphalt has a solid content of 57% and accounts for 7.3% of the total mass of the cold-mix drainage asphalt mixture. Mineral aggregates and fillers account for 92.5%, and fibers account for 0.2%.

[0043] The components of the high-performance modified emulsified asphalt are as follows: 55 parts of No. 70 base asphalt, 1.6 parts of quaternary ammonium salt cationic emulsifier, 5.0 parts of polyurethane modifier, 0.5 parts of calcium chloride and organosilicon, and 37.9 parts of deionized water.

[0044] The mineral aggregate is granite, the filler is limestone powder, and the fiber is polyester fiber. The synthetic gradation of the mineral aggregate is based on a particle size ratio of (11~15) mm:(6~10) mm:(0~5) mm = 15%:46%:36%. The synthetic gradation meets the requirements of 100% passing rate through a 16.0 mm sieve, 96.5% passing rate through a 13.2 mm sieve, and 73.5% passing rate through a 9.5 mm sieve (see Table 2 for specific gradation data).

[0045] Table 2 Synthetic Gradation and Gradation Range

[0046] The preparation process of the cold-mix drainage asphalt mixture in this embodiment is as follows: (1) Heat the base asphalt to 160°C, add polyurethane modifier, stir at a constant temperature and high speed of 12000 rpm for 80 min, and develop at a constant temperature for 120 min to obtain modified asphalt.

[0047] (2) Mix the emulsifier with deionized water and heat to 60°C. After stirring to dissolve, adjust the pH to 3 and add calcium chloride to obtain the emulsifier solution.

[0048] (3) The modified asphalt and emulsifier solution are mixed in proportion, sheared and emulsified at 180°C, and an organosilicon defoamer is added to obtain high-performance modified emulsified asphalt.

[0049] (4) After the mineral aggregate is dried, it is dry-mixed for 5 seconds, high-performance modified emulsified asphalt and fiber are added and mixed for 90 seconds, and then 3% mineral powder is added and mixed for 90 seconds to obtain the mixture.

[0050] (5) Compact Marshall specimens and rut plate specimens were formed, cured and shaped, and then their performance was tested. The test results and index requirements are summarized in Table 3.

[0051] The results show that the porosity of the asphalt mixture in this embodiment reaches 17.5%, the permeability coefficient reaches 3700 mL / min, and the permeability performance is good; the residual stability, scattering loss rate and freeze-thaw splitting strength ratio can all meet the expectations, and it has good water stability; the crack resistance performance (OT test) test loads more than 1400 times, and it has good crack resistance and durability. Example 4:

[0052] This embodiment of the cold-mix drainage asphalt mixture includes high-performance modified emulsified asphalt, mineral aggregates, fillers, and fibers. The high-performance modified emulsified asphalt has a solid content of 57% and accounts for 7.3% of the total mass of the cold-mix drainage asphalt mixture. Mineral aggregates and fillers account for 92.5%, and fibers account for 0.2%.

[0053] The components of the high-performance modified emulsified asphalt are as follows: 55 parts of No. 70 base asphalt, 1.6 parts of quaternary ammonium salt cationic emulsifier, 4.0 parts of polyurethane modifier, 1.0 part of SBS IC modifier, 0.5 parts of calcium chloride and organosilicon, and 37.9 parts of deionized water.

[0054] The preparation process of the cold-mix drainage asphalt mixture in this embodiment is as follows: (1) Heat the base asphalt to 140°C, add polyurethane modifier and SBS IC modifier in sequence, stir at 10000 rpm for 60 min, and keep at a constant temperature for 120 min to obtain modified asphalt.

[0055] (2) Mix the emulsifier with deionized water and heat to 60°C. After stirring to dissolve, adjust the pH to 2.5 and add calcium chloride to obtain the emulsifier solution.

[0056] (3) The modified asphalt and emulsifier solution are mixed in proportion, sheared and emulsified at 180°C, and an organosilicon defoamer is added to obtain high-performance modified emulsified asphalt.

[0057] (4) After the mineral aggregate is dried, it is dry-mixed for 5 seconds, and high-performance modified emulsified asphalt, fiber and mineral powder are added in sequence and stirred for 90 seconds to obtain the mixture.

[0058] (5) Roller-rolled rutted slab specimens were cured and molded, and performance tests were conducted. The test results and index requirements are summarized in Table 3.

[0059] The results show that the porosity of the asphalt mixture in this embodiment reaches 16.8%, the permeability coefficient reaches 3400 mL / min, and the permeability performance is good; the residual stability, scattering loss rate and freeze-thaw splitting strength ratio can all meet the expectations, and it has good water stability; the crack resistance performance (OT test) test loads more than 1400 times, and it has good crack resistance and durability.

[0060] Comparative Example 1: The aggregate gradation of this comparative cold-mix drainage asphalt mixture is (10~15)mm:(6~10)mm:(0~5)mm:mineral powder:fiber = 15%:46%:36%:3%:0.2% (external admixture), which is the same as in Example 1.

[0061] Limestone ore powder and polyester fiber are used.

[0062] In this comparative example, the solid content of emulsified asphalt is 60%; the composition of emulsified asphalt includes base asphalt, emulsifier, stabilizer, defoamer, water, etc., and does not contain polymer modifier, and the emulsified asphalt accounts for 6.3% of the total mass of cold-mixed drainage asphalt mixture.

[0063] The formulation ratio of emulsified asphalt is 60 parts by weight of base asphalt, 1.2 parts by weight of emulsifier, 0.5 parts by weight of stabilizer and defoamer, and 38.3 parts by weight of water.

[0064] The preparation method of cold-mixed drainage asphalt mixture in this embodiment is as follows: (1) Mix cationic emulsifier with deionized water, heat to 60°C, stir until completely dissolved, adjust pH to 3, and add stabilizer; (2) Pump preheated base asphalt and emulsifier aqueous solution into the grinding chamber of high-speed colloid mill in proportion, and shear emulsify at 160°C, adding defoamer during the process to prepare emulsified asphalt; (4) Configure mineral aggregate according to synthetic gradation and dry, dry mix for 5s, add emulsified asphalt and 0.2% polyester fiber, stir for 90s, and finally add 3% mineral powder and stir for 90s to obtain a uniformly mixed cold-mixed drainage asphalt mixture. Add to Marshall specimen mold or rutting plate mold, compact each side 50 times or roll into shape to obtain Marshall specimen or rutting plate specimen, and conduct performance tests. The test results and index requirements are shown in Table 3.

[0065] The difference between this comparative example and Example 1 is that ordinary emulsified asphalt without polymer modifiers was used. As shown in Table 3, its stability (3.5 kN), crack resistance (500 cycles), and standard runoff loss (16%) are all significantly worse than those of Example 1. This proves that the polymer modifier is the key component in this invention for solving the core technical obstacle of low strength in cold-mixed asphalt.

[0066] Comparative Example 2: This comparative example increases the amount of base asphalt to 70 parts and reduces water to 25.3 parts (beyond the scope of the claims). During the preparation process, it was found that the mixture could not form a stable emulsion system, exhibiting rapid stratification or demulsification, rendering it unusable for construction. This indicates that the component ratios of the present invention represent an optimized critical range, which is a necessary condition for ensuring the workability and storage stability of the emulsified asphalt.

[0067] Comparative Example 3: The synthetic gradation of the mineral aggregates was adjusted to have a passing rate of 95% for a 16.0 mm sieve, 77% for a 13.2 mm sieve, 55% for a 9.5 mm sieve, 18% for a 4.75 mm sieve, 14% for a 2.36 mm sieve, 12% for a 1.18 mm sieve, 10% for a 0.6 mm sieve, 8% for a 0.3 mm sieve, 7% for a 0.15 mm sieve, and 4% for a 0.075 mm sieve.

[0068] Other parameters remain the same as in Example 1.

[0069] The test results are shown in Table 3.

[0070] Table 3 Comparison of properties of cold-mixed drainage asphalt mixtures

[0071] Comparative Example 3 altered the gradation of the mineral aggregate (beyond the scope of the claims). The results showed that although the porosity (23.2%) and permeability coefficient (3800 mL / min) were high, the stability (2.8 kN) and crack resistance (500 cycles) deteriorated sharply. This demonstrates that the fine gradation range defined in this invention is crucial for balancing drainage and mechanical properties; while an excessively coarse gradation provides better drainage, it results in a loose skeleton, unable to withstand aircraft loads.

[0072] The inventors further verified the applicability of the obtained cold-mixed drainage asphalt mixture in the actual construction of airport pavement and whether the key properties such as drainage and mechanical properties after molding meet the requirements of airport pavement drainage base course.

[0073] The material adopts the cold-mix drainage asphalt mixture formulation of Example 3, which includes high-performance modified emulsified asphalt, granite aggregate, limestone powder, and polyester fiber.

[0074] The equipment includes an automatic leveling paver, a 13t steel wheel roller, an in-situ permeability meter, a road surface evenness meter, and a rebound modulus tester.

[0075] The experimental steps are as follows: (1) Base treatment: Sweep the surface of cement-stabilized crushed stone base, remove floating dust and debris, keep the surface clean, and then spread tack coat and tack coat.

[0076] (2) Mixing of the mixture: Mix the cold-mixed drainage asphalt mixture on site according to the proportions in Example 3 to ensure that all components are mixed evenly.

[0077] (3) Paving and compaction: The paving is carried out using an automatic leveling paver, with the paving thickness controlled at 4cm, and then compacted using a 13t steel wheel roller.

[0078] (4) Curing: After the emulsified asphalt breaks down and solidifies, it should be naturally cured for 7 days.

[0079] (5) Performance testing: After the curing is completed, five different test points are selected at the construction site to conduct in-situ water seepage test, flatness test and rebound modulus test respectively.

[0080] Experimental results show that: In-situ permeability performance: The average permeability coefficient of the 5 test points was 4576 mL / min, which is far higher than the technical requirement of ≥2000 mL / min. This indicates that the mixture still has excellent drainage performance after actual construction and can quickly drain the water accumulated inside the airport pavement.

[0081] Smoothness: Test results show that the road surface smoothness deviation is ≤3mm / 3m, which meets the airport pavement smoothness requirements and ensures the stability of aircraft operation.

[0082] Resilient modulus: The average resilient modulus reaches 2800MPa, indicating that the mixture has good mechanical bearing capacity after molding, can withstand the load of aircraft, and meets the mechanical performance requirements of airport pavement base course.

[0083] This experiment, through on-site construction and performance testing, verified that the cold-mixed drainage asphalt mixture has good construction adaptability, and after molding, it has high-efficiency drainage performance, excellent mechanical bearing capacity and smoothness, which fully meets the usage requirements of airport pavement drainage base course, can effectively reduce water damage to airport pavement and extend pavement service life.

[0084] Furthermore, field engineering applications have shown that the cold-mixed drainage asphalt mixture obtained by this invention can be used to set a drainage asphalt functional layer inside the airport pavement structure. It can also prevent the cement concrete surface layer from bonding with the base layer, reduce the temperature warping deformation and stress on the pavement slab by more than 20%, reduce the risk of concrete pavement breakage, and improve the durability of the concrete pavement, among other outstanding advantages.

[0085] The above specific embodiments further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A cold-mix drainage asphalt mixture for airport cement pavement, characterized in that, It includes the following components in parts by weight: 5.4 to 9 parts modified emulsified asphalt, 90.8 to 95.6 parts mineral aggregate and filler, and 0.2 to 0.4 parts fiber; The modified emulsified asphalt comprises the following components in parts by weight: 45 to 62 parts base asphalt, 0.8 to 1.5 parts emulsifier, 3 to 5 parts polymer modifier, 0.2 to 0.5 parts stabilizer and defoamer by weight, and 35 to 50 parts water.

2. The cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The base asphalt is at least one of grade 70 base asphalt, grade 90 base asphalt, PG 64-22 base asphalt, and PG58-22 base asphalt.

3. The cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The emulsifier is a quaternary ammonium salt cationic emulsifier.

4. The cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The polymer modifier is at least one of styrene-butadiene-styrene block copolymer, polyethylene, styrene-butadiene rubber latex, polyurethane, and epoxy resin.

5. A cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The stabilizer is at least one of calcium chloride and polyvinyl alcohol, and the defoamer is organosilicon.

6. A cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The total mass of the mineral aggregates and fillers accounts for 90.8% to 95.6% of the total mass of the cold-mixed drainage asphalt mixture, and the fiber accounts for 0.2% to 0.4% of the total mass of the cold-mixed drainage asphalt mixture.

7. A cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The mineral aggregate is at least one of limestone, granite, and basalt; and / or the filler is mineral powder; and / or the fiber is polyester fiber, lignin fiber, or nanocellulose.

8. A cold-mix drainage asphalt mixture for airport cement pavement according to claim 1, characterized in that, The synthetic gradation range of the mineral aggregates meets the following requirements: 100% passing through a 16.0 mm sieve, 90%~100% passing through a 13.2 mm sieve, 60%~80% passing through a 9.5 mm sieve, 12%~30% passing through a 4.75 mm sieve, 10%~22% passing through a 2.36 mm sieve, 6%~18% passing through a 1.18 mm sieve, 4%~15% passing through a 0.6 mm sieve, 3%~12% passing through a 0.3 mm sieve, 3%~8% passing through a 0.15 mm sieve, and 2%~6% passing through a 0.075 mm sieve.

9. A method for preparing a cold-mixed drainage asphalt mixture for airport cement pavement according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Heat the base asphalt to 140-165℃, add the polymer modifier one by one, stir at high speed for 40-60 min at constant temperature, and develop at constant temperature for 60-120 min to make modified asphalt; (2) Mix the emulsifier with water, heat to 50-60℃, stir until completely dissolved, adjust the pH to 2-3, add the stabilizer, and obtain the emulsifier solution; (3) Mix the preheated modified asphalt in step (1) with the emulsifier solution obtained in step (2) in proportion, and shear emulsify at 140-160℃. Add defoamer during the process to obtain high-performance modified emulsified asphalt. (4) After mixing the high-performance modified emulsified asphalt with dry mineral aggregates, fillers and fibers at room temperature according to the specified ratio, the mixture is then laid and compacted in sequence. (5) Wait for the emulsified asphalt to break down and solidify, and then cure and shape it.

10. A method for preparing a cold-mixed drainage asphalt mixture for airport cement pavement according to claim 9, characterized in that, In step (1), the constant temperature high-speed mixing rate is 8000-12000 rpm, and in step (4), the thickness of the road surface layer obtained after compaction is 4~6 cm.